35th Aerospace Sciences Meeting and Exhibit 1997
DOI: 10.2514/6.1997-826
|View full text |Cite
|
Sign up to set email alerts
|

Numerical computation of flapping-wing propulsion and power extraction

Abstract: Numerical procedures are presented for the systematic computation of unsteady ows over moving airfoils or airfoil combinations, and these procedures are applied to the investigation of apping-wing propulsion and power extraction. Flow solutions about single foils are computed using an unsteady, t wo-dimensional panel code coupled with a boundary layer algorithm and driven using an interactive graphical user interface. Flow solutions about airfoil combinations are computed using a companion, multi-element v ers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
88
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(90 citation statements)
references
References 19 publications
1
88
0
1
Order By: Relevance
“…This was studied in some detail in Ref. 23, where it was shown that the propulsive performance of a apping foil was signi cantly enhanced near a ground plane. This opposing-plunge or ground-e ect con guration o ers the additional benets of mechanical and aerodynamic balanced loading in the vertical direction, and is therefore desirable for our wind-tunnel model.…”
Section: Con Gurationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was studied in some detail in Ref. 23, where it was shown that the propulsive performance of a apping foil was signi cantly enhanced near a ground plane. This opposing-plunge or ground-e ect con guration o ers the additional benets of mechanical and aerodynamic balanced loading in the vertical direction, and is therefore desirable for our wind-tunnel model.…”
Section: Con Gurationsmentioning
confidence: 99%
“…Jones et al 7 compared wake structures behind apping wings experimentally photographed and numerically predicted, and demonstrated that the formation and evolution of these unsteady wakes is essentially an inviscid phenomenon over a broad range of Strouhal numbers. Jones and Platzer 23 performed extensive n umerical apping-wing propulsion calculations using panel methods, and found a large performance enhancement for an airfoil apping in ground e ect, an e ect often utilized by birds.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous authors have studied the problem of a 2D airfoil in pure heaving motion, in which the airfoil oscillates vertically with a zero angle of attack [Jones and Platzer, 1997, Wang, 2000, Lewin and Haj-Hariri, 2003, Lua et al, 2007, Wei and Zheng, 2014, Choi et al, 2015. This simplified configuration is still a rich model where some of the main features of flapping flight are present, for example, the leading and trailing edge vortices.…”
Section: Introductionmentioning
confidence: 99%
“…Obviously, the two scenarios can be considered as the cases with opposite phase lags between the pitching and plunging motions. It should be noted that, as reported in Jones and Platzer (1997) and Schouveiler et al (2005), a better propulsive performance can be achieved when a suitable phase lag was adopted for an airfoil in combined pitching and plunging motion. It is well known that the generation of wake vortices near the airfoil trailing edge is due to the pressure differences between the upper and lower sides of the pitching airfoil.…”
Section: Discussionmentioning
confidence: 97%